The Critique of Fakhr al-Din al-Razi's Reasons for Non-Teleology for Divine Acts - Hasan Moradi (آموزه‌‌های فلسفه اسلامي, 2019)
The teleology of an agent or a thing is one of the most important theological (kalami) and philosophical issues that one of its most preeminent branches is the purpose of the divine acts (afa'al). Fakhr al-Din al-Razi has propounded several arguments for the voidance of God's purposing that they are stated in three categories. In the first group, God's purpose is inconsistency with some of His attributes such as perfection or being the absolute power and act being temporally created and in the second group, it is incompatible with human attributes such as the boundary of asking question, limitation in understanding and being under obligation. The third group, it is believed that purposiveness establishes paradox. In this paper, meanwhile criticizing every argument, on the whole it is obtained that more arguments has invalidated the Muʿtazila's opinion about the purposing extraneous to the divine essence not essential purposiveness as philosopher like Ibn Sina (Avicenna) has put forward.